Plane wave propagation in exponentially graded isotropic non local generalized thermoelastic solid medium under initial stress and gravity - Kumar, Krishan; Malik, Sangeeta; Antil, Ankush (Zielona Góra: Uniwersytet Zielonogórski)
The work is concerned with the propagation of plane waves at the free half space in a exponentially graded isotropic nonlocal generalized thermoelastic solid medium under initial stress and gravity. We study the incidence of P or SV waves at the free half space. We found three reflected waves namely P, thermal T and SV waves propagating with different speeds. The phase speeds, reflection and energy coefficients are calculated in closed form to study the impact of gravity and initial stress parameter on reflection and energy coefficients. These are calculated numerically and shown graphically with the help of MATLAB. Some special cases of interest are also drawn from the present investigation.
Keywords: thermoelasticity; non-local; initial stress; exponential graded